In silico and in vitro chemometrics, cell toxicity and permeability of naringenin 8-sulphonate and derivatives - Macedo, Tiago; Paiva-Martins, Fátima; Valentão, Patrícia; Pereira, David M. (Frontiers in Pharmacology, 2024)
Background: Sulphur containing natural compounds are among the most biologically relevant metabolites in vivo. Naringenin 8-sulphonate from Parinari excelsa Sabine was evaluated in a previous work, demonstrating ability to act as a natural anti-inflammatory. Although the interference of this molecule against different inflammatory mediators was described, there is no information regarding its potential toxicity and pharmacokinetics, which are essential for its capacity to reach its therapeutic targets. In fact, despite the existence of reports on naringenin ADMET properties, the influence of sulphation patterns on them remains unknown.Objectives: This work aims to assess the in vitro pharmacokinetic and toxicological behavior of naringenin 8-sulphonate, as well as to understand the importance of the presence and position of the sulphur containing group for that.Methods: Naringenin 8-sulphonate physicochemical and ADMET properties were investigated using in silico tools and cell-based in vitro models. At the same time, naringenin and naringenin 4'-Osulphate were investigated to evaluate the impact of the sulphonate group on the results. ADMETlab 2.0 in silico tool was used to predict the compounds' physicochemical descriptors. Pharmacokinetic properties were determined experimentally in vitro. While MRC-5 lung fibroblasts and HaCaT keratinocytes were used to evaluate the cytotoxicity of samples through MTT and LDH assays, Caco-2 human intestinal epithelial cells were used for the determination of genotoxicity, through alkaline comet assay, and as a permeability model to assess the ability of compounds to cross biological barriers.Results: Experimental determinations showed that none of the compounds was cytotoxic. In terms of genotoxicity, naringenin 8-sulphonate and naringenin caused significant DNA fragmentation, whereas naringenin 4'-O-sulphate did not. When it comes to permeability, the two sulphur-containing compounds with a sulphur containing group were clearly less capable to cross the Caco-2 cell barrier than naringenin.In this study, we conclude that the sulphur containing group from naringenin 8-sulphonate is disadvantageous for the molecule in terms of ADMET properties, being particularly impactful in the permeability in intestinal barrier models. Thus, this work provides important insights regarding the role of flavonoids sulphation and sulphonation upon pharmacokinetics and toxicity.